Visualizing Groundwater Dispersion: Laboratory Exercise on Dispersivity with Hands-on and Online Students - Korom, Scott (International Journal of Engineering Pedagogy (iJEP), 2022)
Longitudinal groundwater dispersion is measured by calculating the spreading of a solute in the direction of groundwater flow as a function of time, with dispersivity being the plume dispersion divided by the groundwater velocity. Two-dimensional physical groundwater flow models were used in a laboratory exercise to illustrate groundwater dispersion to hands-on and online students. Learning assessment of the pedagogical value of the laboratory exercise was based on a student survey and an independent laboratory assignment graded by the course instructor. Both tools indicated that student learning was effectively enhanced by the dispersivity laboratory exercise; however, it was more effective for the hands-on students.